Short-term branched-chain amino acid supplementation does not enhance vertical jump in professional volleyball players. A double-blind, controlled, randomized study - Martín-Martínez, J. P.; Calleja-Gonzalez, J.; Adsuar Sala, J. C.; Gómez-Pomares, S.; Carlos-Vivas, J.; Pérez-Gómez, J. (Nutrición Hospitalaria, 2020)
To the best of the authors` knowledge, no previous studies have described the effect of branched-chain amino acids (BCAA) on vertical performance during a week in professional volleyball players. This study assessed BCAA supplementation for a week, aiming to improve vertical jump performance in male professional volleyball players. Twelve male volleyballers were randomly assigned to a BCAA group (n = 6) or a control group (n = 6). The BCAA group ingested 21 g over a week, 7 g per day on Monday, Wednesday, and Friday, before a volleyball training session, while the control group drank a placebo drink. Participants performed 8 maximal countermovement jumps (CMJ); the 3 CMJs on Monday and Wednesday were evaluated after warm-up, after plyometric training, and at the end of the training session; and the 2 CMJs on Friday were evaluated after warm-up, and at the end of the training session. Compared with baseline, no significant differences in CMJ over the week were observed in BCAA or control group, neither between groups. The results indicated that 21 g of BCAA supplementation over a week did not improve vertical jump performance in professional volleyball players.